Cioccolato / Presantia Bujang ... [et al.] - Bujang, Presantia; Zosen, Belinguer; Ahmad Daud, Khairunnisa; Jeffry, Nurul Amira (2014)
Cioccolato is a partnership business that consists of four partners where they share the same interest and passion in chocolate. The four partners are the General 'Tanager, Administration Manager, Marketing Manager, Operation Manager, and Financial Manager. Cioccolato is a business mainly based on selling every luxuries type of chocolate as our product. Mostly, we import our entire product from overseas. The brand that we often choose is Toucher, Godiva, Lindt. Donckels, Daim, Beryl, Toblerone, Mars, Hershey’s, and Daiana. Our market targets are children, young adults, and adult that comes from intermediate and high-income family that crave for luxury chocolate. Usually, woman and children really favour chocolate because chocolate makes them feel loved and special besides the tastiness. The uniqueness of our business is we offer luxury chocolate which not practically found in any groceries store and rare in the market. Other services that we have are seasonal and special promotions. Seasonal promotions are such as during Valentine’s Day, and Chinese New Year. We usually offering hamper packaging which full with branded chocolate and present for those seasonal promotion. We decided our location to be at shop lot in front of Medan Mall, Mukah. It is strategic place where it is located in the centre of town Mukah. Furthermore, Medan Mall is the first mall in Mukah. Thus, for sure customer will go there and they will notice our shop that only in front of Medan Mall. The location also near to the neighbourhood and university at Mukah. Hence, it will be easier for the customers to stop by at our shop. We expected to increase the number of customer and gain profit since we are the only chocolate shop in Mukah. We aim to be the famous chocolate shop in Mukah. We hope in the future we can expand our business in other states or other town and our sales boosting to the maximum.